2018
DOI: 10.1016/j.jaip.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Asthma Control Test Questionnaire Among Smoking Asthmatics

Abstract: The ACT questionnaire was reliable and discriminated between levels of asthma control in smoking asthmatics with similar sensitivity and specificity as nonsmoking asthmatics, which confirms its value as a tool for the management of asthma in this prevalent but understudied subgroup of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“… 37 An ACT score of 19 provided an optimum balance of sensitivity (71.3%) and specificity (70.8%) for detecting poorly controlled asthma in non-smokers 37 and a score of 18.6 provided the maximum area under the receiver operator characteristic curve in smokers. 38 The asthma symptom questions in the PATH Study were validated by demonstrating that self-reported asthma symptom severity was associated with functional status, and prevalence of asthma symptoms (wheeze) was similar to the prevalence of symptoms in NHANES (see online supplemental appendix 1 ). People with asthma were also asked whether they used asthma medications in the past 12 months (‘treated asthma’) and what class of medications they regularly used.…”
Section: Methodsmentioning
confidence: 99%
“… 37 An ACT score of 19 provided an optimum balance of sensitivity (71.3%) and specificity (70.8%) for detecting poorly controlled asthma in non-smokers 37 and a score of 18.6 provided the maximum area under the receiver operator characteristic curve in smokers. 38 The asthma symptom questions in the PATH Study were validated by demonstrating that self-reported asthma symptom severity was associated with functional status, and prevalence of asthma symptoms (wheeze) was similar to the prevalence of symptoms in NHANES (see online supplemental appendix 1 ). People with asthma were also asked whether they used asthma medications in the past 12 months (‘treated asthma’) and what class of medications they regularly used.…”
Section: Methodsmentioning
confidence: 99%
“…The ACT consists of five questions with five possible answers: 20–25 correlates with well controlled asthma; anything less than 19 represents uncontrolled asthma. The minimally important clinical difference (MCID) is 3 points 14 . Data was collected at 3 (2–4 months), 6 (5–7 months), and >12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The minimally important clinical difference (MCID) is 3 points. 14 Data was collected at 3 (2-4 months), 6 (5-7 months), and >12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents whose asthma was found as controlled or completely controlled were grouped during the analysis. The ACT has been validated on smoker participants [ 13 ]. Therefore, in this research, an ACT-validated Arabic edition was used [ 14 ].…”
Section: Methodsmentioning
confidence: 99%